Pengaruh Cafe Atmosphere terhadap Keputusan Pembelian Gen Y pada Old Bens Cafe - Albert Kurniawan Purnomo (Universitas Kristen Maranatha, 2017)
The purpose of this study is to examine and analyze the effect of the elements cafe atmosphere to Purchase Decision on Gen Y in Coffee & Dessert Cafe Old Bens Bandung. Trend adolescence and young adulthood era milinieum are critical thinking, and want freedom. Freedom in choosing which is considered comfort will have an impact on the purchase decision. Purchasing decisions are influenced by the atmosphere of the place, and here demanded creativity cafe owners to be able to turn the atmosphere through the concept Cafe Atmosphere. This research is a quantitative, approach to causal explanatory. Data were collected by distributing questionnaires. Samples obtained were 62 respondents with purposive random sampling technique. Results obtained state that element Store Layout and exterior of variables Cafe Atmosphere influence on purchase decision.Â Keywords: Cafe Atmosphere; Exterior; Purchase Decision; Store Layout